Atropelamento de fauna: divulgando a ciência - Matsushige, Helena (2021)
It’s understood by scientific divulgation the process of dissemination of scientific knowledge through the use of simple language, understandable to the uninitiated people in science. Furthermore, scientific popularization aims to make science popular, that is, tangible to the population. Science provides to the citizens useful knowledge to decision making in daily life. The Internet is currently a powerful means of communication, being an important diffuser of information. Regarding fauna roadkill, it’s known by literature that one of the most important reasons of accidents is lack of conscience. Being some drivers imprudent and others ignorant about the consequences of this act. This thesis was formed by the realization of initial questionnaire about the topic “Faunal Roadkill” and divulgation of scientific results on the theme. That took place throughout the most used virtual means of communication of those voluntaries. The questionnaire applied made possible to characterize the profile of the participants, who are in their majority from the state of São Paulo, are at least studying at university, transit daily or weekly through roads, and prefer Instagram, which was the social media selected to divulgate the scientific information. Those drivers are between 27 and 43 years old, have license to drive a car and are not professional drivers. The questions about the topic show that the public has knowledge about public policies, which implemented have the potential to decrease roadkill. However, they ignore the measures which each citizen individually can apply to reduce those impacts and their effects in the ecosystem. Based on this identify lack of knowledge, divulgation was carried on, and a second questionnaire (post scientific divulgation) was posted on the same account on Instagram, targeting the evaluation of the efficiency of the data disclosed. On this second questionnaire there were not enough answers (post scientific divulgation) to elaborate a comparison of the efficiency of the scientific divulgation, probably because Instagram was not used efficiently to do the divulgation. For further studies, it is recommended a more dynamic use of social media, exploring more the tools of this resource. Despite the failure of the evaluation of the efficiency of scientific divulgation (second questionnaire), the methodology adopted on the first questionnaire was an efficient tool, making possible an evaluation of knowledge about specific themes, making possible the planning of the divulgation of information and results of scientific research, and also the clarification of some themes on the topic.